2002
DOI: 10.1046/j.1365-2427.2002.00827.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and emergence of the stonefly Leuctra nigra in coniferous forest streams with contrasting pH

Abstract: 1. Growth and emergence of the acidification tolerant stonefly Leuctra nigra were studied in four coniferous forest streams with contrasting pH. Invertebrate samples were taken bimonthly during May 1997 to April 1998. Emerging L. nigra were captured in two of the streams during April to July 1998 using pyramidal emergence traps. In addition, a laboratory experiment was conducted to evaluate growth of L. nigra in response to variations in food quality (neutral or acid conditioned leaves) and water pH. 2. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 54 publications
(76 reference statements)
3
34
0
1
Order By: Relevance
“…Changes in larval food sources and stream physicochemical conditions associated with afforestation of riparian areas influence the size of adults at emergence indirectly through reductions in larval growth rates (Sweeney, 1984;Weatherley and Ormerod, 1990;Sweeney, 1993;Thomsen and Friberg, 2002). The smaller size at metamorphosis achieved by species in forested streams is linked to reductions in adult longevity, fecundity and reproductive success (Peterssen, 1987;Flecker et al, 1988;Taylor et al, 1998).…”
Section: From Larva To Adult Growing Up With Issuesmentioning
confidence: 99%
“…Changes in larval food sources and stream physicochemical conditions associated with afforestation of riparian areas influence the size of adults at emergence indirectly through reductions in larval growth rates (Sweeney, 1984;Weatherley and Ormerod, 1990;Sweeney, 1993;Thomsen and Friberg, 2002). The smaller size at metamorphosis achieved by species in forested streams is linked to reductions in adult longevity, fecundity and reproductive success (Peterssen, 1987;Flecker et al, 1988;Taylor et al, 1998).…”
Section: From Larva To Adult Growing Up With Issuesmentioning
confidence: 99%
“…Harriman & Morrison, 1982;Vuori & Joensuu, 1996;Dangles & Guérold, 2000;Guérold et al, 2000;Thomsen & Friberg, 2002;Kowalik & Ormerod, 2006). Many studies have found a relationship between conifer forest plantation cover and macroinvertebrate composition, with an absence of Ephemeroptera related to forest-mediated acidification (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The organismic stress from acidity results from a failure of ionic regulation (Vangenechten et al, 1989) and a passive uptake of metals from water (DeNicola & Stapleton, 2002). Sub-lethal effects could be mediated by low food quality (Thomsen & Friberg, 2002). Primary production and bacterial decomposition decrease (Økland & Økland, 1986;Niyogi et al, 2002;Dangles et al, 2004).…”
Section: Introductionmentioning
confidence: 99%